0185 Relationships between Dietary Supplement Intake and Sleep Duration, Insomnia, and Fatigue. (27th April 2018) - Sanchez, C; Hale, L; Branas, C; Gallagher, R; Killgore, W; Gehrels, J; Alfonso-Miller, P; Grandner, M
Abstract: Introduction: Dietary supplements are taken by many U.S. adults, often to improve or maintain health. Approximately 10% of adults use supplements to increase energy levels but few take supplements to improve sleep, despite being marketed for better sleep. Prevalence estimates of disturbed sleep range from 35–41% among adults. This study examines the association between dietary supplement intake and sleep duration, insomnia, and fatigue. Methods: Data from the Sleep and Healthy Activity, Diet, Environment, and Socialization (SHADES) study was used. The study was community-based, in Pennsylvania (N=1007 adults). Covariates included age, sex, race/ethnicity, education, income, body mass index, overall health, and perceived stress. Multinomial logistic regression was used to determine the relationship between supplement use (categorized as any use, multivitamin, vitamin B, vitamin C, vitamin D, calcium, omega-3 fatty acids, botanicals, probiotics, and others) and sleep duration (hours of sleep in a typical 24-hour period, assessed using the item from the Behavioral Risk Factor Surveillance System), insomnia (using the Insomnia Severity Index), and fatigue (using the Fatigue Severity Scale). Results: Any use of supplements was associated with a lower likelihood of very short sleep (OR=0.3, 95%CI[0.2, 0.8], p=0.008) in adjusted analyses. Multivitamin use was associated with a lower likelihood of very short sleep (OR=0.2, 95%CI[0.1, 0.7], p=0.008) and long sleep (OR=0.6, 95%CI[0.3, 1.0], p=0.04). Vitamin B was associated with increased likelihood of mild insomnia (OR=2.0, 95%CI[1.0, 3.8], p=0.04) in adjusted analyses. Probiotic use was associated with higher fatigue scores (B=7.4, 95%CI[1.62, 13.17], p=0.01). Conclusion: Multivitamin use was associated with a decreased likelihood of both very short and long sleep, likely reflecting an increased interest in health. It is unclear why Vitamin B was associated with an increased likelihood of mild insomnia or why probiotic use is associated with fatigue. Support (If Any): The SHADES study was funded by R21ES022931